Calculation of pressure loss and critical velocity for slurry flows with additive agents in vertical polyethylene pipelines - Semenenko Yevhen; Kril Stepan; Medvedieva Olha; Nykyforova Nina; Tatarko Larysa (E3S Web of Conferences, 2019)
The method of determination of parameters of hydrotransport of solid polydisperse materials in vertical pipelines is offered. The reasons of discrepancy between estimated and observed data when using A. Smoldyrev’s method for calculation of hydraulic gradient and critical velocity in vertical steel pipelines are analysed. Particularly non-applicability of Velicanov principle to hydrotransport of solid materials in vertical pipelines is proved and contribution of particles fall velocity to the value of complementary hydraulic gradient in vertical pipelines is estimated. Suggested formulas for calculation of hydraulic gradient and critical velocity in vertical pipelines are multipurpose because they may be used for calculation of hydrotransport parameters in steel and polymeric vertical pipelines with using of friction reducing agents and without it. The method for parameters calculation of solid materials hydrotransport in vertical polymeric pipelines is first offered. Elaborated formulas ensure also increasing of accuracy of calculations.